Pyroptosis and gasdermins—Emerging insights and therapeutic opportunities in metabolic dysfunction-associated steatohepatitis - Stoess, Christian; Leszczynska, Aleksandra; Kui, Lin; Feldstein, Ariel E. (Frontiers in Cell and Developmental Biology, 2023)
In recent years, there has been a rapid expansion in our understanding of regulated cell death, leading to the discovery of novel mechanisms that govern diverse cell death pathways. One recently discovered type of cell death is pyroptosis, initially identified in the 1990s as a caspase-1-dependent lytic cell death. However, further investigations have redefined pyroptosis as a regulated cell death that relies on the activation of pore-forming proteins, particularly the gasdermin family. Among the key regulators of pyroptosis is the inflammasome sensor NOD-like receptor 3 (NLRP3), a critical innate immune sensor responsible for regulating the activation of caspase-1 and gasdermin D. A deeper understanding of pyroptosis and its interplay with other forms of regulated cell death is emerging, shedding light on a complex regulatory network controlling pore-forming proteins and cell fate. Cell death processes play a central role in diseases such as metabolic dysfunction-associated steatotic liver disease, metabolic dysfunction-associated steatohepatitis, autoinflammatory disorders, and cancer. Cell death often acts as a starting point in these diseases, making it an appealing target for drug development. Yet, the complete molecular mechanisms are not fully understood, and new discoveries reveal promising novel avenues for therapeutic interventions. In this review, we summarize recent evidence on pathways and proteins controlling pyroptosis and gasdermins. Furthermore, we will address the role of pyroptosis and the gasdermin family in metabolic dysfunction-associated steatotic liver disease and steatohepatitis. Additionally, we highlight new potential therapeutic targets for treating metabolic dysfunction-associated steatohepatitis and other inflammatory-associated diseases.